Fabrication and Compression Properties of Reinforced Epoxy Syntactic Foam With Basalt Fiber - Shuai Cao; Tao Jiang; Shanshan Shi; Xiaofan Gui; Ying Wang; Bo Tang; Lixue Xiang; Xuming Dai; Donghai Lin; Ning Zhong; Wenge Li; Jinhong Yu; et al. (Advances in Polymer Technology)
Deep-sea equipment is generally made of lightweight and pressure-resistant materials in order to meet the requirements of the actual work. In order to explore marine resources better, it is necessary to research lightweight buoyancy materials for loading on mining equipment. These buoyancy materials contribute not only to providing adequate buoyancy to the mining equipment but also to reducing economic expenses. In this paper, hollow glass microspheres reinforced epoxy hollow spheres (HGMSs-EHSs) were prepared by the rolling ball method using expanded polystyrene (EPS), epoxy resin (EP), and HGMS as raw materials. Epoxy syntactic foam (ESF) was manufactured by blending EP, curing agent, HGMS, and HGMS-EHS with molding method. Basalt fiber (BF) reinforced ESF was fabricated by adding BFs to form a fiber network inside the syntactic foam. The results revealed that the density and compressive strength of ESF increased progressively with the number of HGMS-EHS layers. The density and compressive strength of ESF decreased prospectively with the increase of the stacking volume fraction of HGMS-EHS. The density and compressive strength of ESF increased gradually with the enlargement of the length and content of BF. In the range of influencing factors mentioned above, the density of ESF remains around 0.3 g/cm3, which has a low density. When the number of layers of HGMS-EHS was two, the stacking volume fraction was 90%, the length of BF was 12 mm, the content of BF was 4%, the density of BF-ESF was 0.316 g/cm3, and the compressive strength was 6.93 MPa. The compressive strength of prepared buoyancy material can meet the pressure resistance requirements for operations in waters of a certain depth. With a density of only 0.316 g/cm3, it provides sufficient buoyancy to balance the gravity of the equipment. Compared with the current study, in this paper, BFs were used as the reinforcing phase to prepare solid buoyancy foam with low density and high compressive strength. The experimental results demonstrate that this economical fiber material can effectively improve the compressive strength of buoyancy materials. This buoyancy material may be suitable for loading on small equipment for extracting marine resources. This work provides a reference for the preparation of low-density solid buoyancy materials.